Return On Asset (Roa) Analysis Using Du Pont System Method In PT. Ultrajaya Milk Industry And Trading Company Tbk” (2015-2018 Period) - Ryzka Pradana Indiyanti (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
The purpose of this study was to determine the value of the company's Return On Assets (ROA) using Du Pont System method. Du Pont System is an integrated approach to financial ratio analysis that combines the ratio of TATO activity with profit ratio, profit margin on the sale of NPM which shows both interacting in determining ROA. The research method used in this research is descriptive method, with data collection techniques carried out by means of documentation. Based on the results of data analysis, shows the value of ROA at PT. Ultrajaya Milk & Trading Company Tbk which is calculated using the Du Pont System analysis is not good, with a value of ROA that has decreased from 2016 by 16.7%, in 2017 amounting to 13.9% and 2018 by 12.6%. This is due to the decrease in the value of NPM and TATO because basically the value of ROA is influenced by NPM and TATO. So that the value of ROA at PT. Ultrajaya Milk Industry & Trading Company Tbk which is calculated using the Du Pont System method is still not effective due to a tendency to decrease ROA value.